PsycEXTRA Dataset 2009
DOI: 10.1037/e721392011-001
|View full text |Cite
|
Sign up to set email alerts
|

Do Assets Help Families Cope with Adverse Events?

Abstract: THE URBAN INSTITUTE Family events, such as a job loss, the onset of health limitations, and a change in family structure, can adversely affect economic well-being. The impact of these events may be mitigated if the family holds assets that it can draw on to maintain consumption and material well-being. This study examines the extent to which families that hold assets are better able to maintain their level of material well-being in the face of adverse events, compared with families that do not hold assets. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 1 publication
4
62
0
Order By: Relevance
“…Having access to at least $500 influenced material hardship equivalent to a threefold increase in household income (Mayer and Jencks 1989). Among households experiencing a financial shock, asset-poor households are 23 percentage points more likely to face material hardship than non-asset-poor families (McKernan et al 2009). Keating (2012) found that the probability of experiencing material hardship is greatest for asset-poor households in the bottom third of the income distribution.…”
Section: Assets As a Mediator Of Financial Shocks And Hardshipmentioning
confidence: 99%
See 4 more Smart Citations
“…Having access to at least $500 influenced material hardship equivalent to a threefold increase in household income (Mayer and Jencks 1989). Among households experiencing a financial shock, asset-poor households are 23 percentage points more likely to face material hardship than non-asset-poor families (McKernan et al 2009). Keating (2012) found that the probability of experiencing material hardship is greatest for asset-poor households in the bottom third of the income distribution.…”
Section: Assets As a Mediator Of Financial Shocks And Hardshipmentioning
confidence: 99%
“…Income shocks are a consistent predictor of material hardship for households (Heflin 2016), yet among lowincome households, the presence of up to $2000 in liquid assets reduces the risk of hardship by 5 percentage points compared to households with no assets (McKernan et al 2009). Additional studies have found reduced odds for material hardship associated with Child Development Account (CDA) participation (Wikoff et al 2015) and reduced financial strain associated with homeownership (Manturuk et al 2012) and greater financial assets among low-income households (Rothwell and Han 2010).…”
Section: Assets As a Mediator Of Financial Shocks And Hardshipmentioning
confidence: 99%
See 3 more Smart Citations